Doświadczalne Studium Kinematyki Ośrodka Sypkiego dla Pewnych Problemów Brzegowych - Szczepiński, W.; Winek, H. (Engineering Transactions, 1972)
The aim of the paper is the experimental verification of various flow rules for granular media. The verification is performed in the case of several particular deformation processes under the plane strain conditions in which relatively simple theoretical velocity fields can be constructed following from various concepts of relations between the stresses and the strain rates. Dry sand has been used as the medium as also a model consisting oftiny glass rods ofvarious diameters. The results reveal a good agreement (for loose media) with the theoretical solutions obtained with the use of flow rule (1.2) assuming the medium to be incompressible and isotropic. The characteristics networks for stresses and velocities are different in that case. In the case of compacted sand the agreement of results is not so good.